Liking but Devaluing Animals: Emotional and Deliberative Paths to Speciesism. Issue 8 (November 2020) - Caviola, Lucius; Capraro, Valerio
We explore whether priming emotion versus deliberation affects speciesism—the tendency to prioritize certain individuals over others on the basis of their species membership (three main and two supplementary studies, four preregistered; N = 3, 288). We find that the tendency to prioritize humans over animals (anthropocentric speciesism) decreases when participants were asked to think emotionally compared to deliberatively. In contrast, the tendency to prioritize dogs over other animals (pet speciesism) increases when participants were asked to think emotionally compared to deliberatively. We hypothesize that, emotionally, people like animals in general and dogs in particular; however, deliberatively, people attribute higher moral status to humans than animals and roughly equal status to dogs, chimpanzees, elephants, and pigs. In support of this explanation, participants tended to discriminate between animals based on likability when thinking emotionally and based on moral status when thinking deliberatively. These findings shed light on the psychological underpinnings of speciesism.